PENGARUH MAKRO EKONOMI DAN MIKRO EKONOMI TERHADAP STRUKTUR MODAL (STUDI EMPIRIS PADA PERUSAHAAN DJARUM GROUP PERIODE 2008-2017) - Misharni Misharni; Fiona Adziliani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
This study aims to determine the Effect Macro Economic and Micro economic on Capital Structure (Empirical Study on Djarum Group Companies 2008-2017). Independent variables are Inflation (X1) and firm size (X2). The dependent variable is Long Term Debt to Equity Ratio (LTDtER) (Y). The sample in this study is a company listed on the Indonesia Stock Exchange, namely the Djarum Group Company for the period 2008-2017. Data is collected using annual financial statement documentation. The data collection tool is the observation of the company’s annual report from the IDX Website. Hypothesis testing uses analysis, multiple linear regression, t test, F test and determination. The results showed that inflation did not effect Long Term Debt to Equity Ratio (LTDtER), p value 0.670. The size of the Company influences Long Term Debt to Equity Ratio (LTDtER) p value 0,000. Inflation and company size simultaneously influence Long Term Debt to Equity Ratio (LTDtER), p value 0,000. In maintaining the survival of the company, the company is expected to form the right strategy in marketing the product when the inflation rate has increased so that it can reduce the impact caused by inflation. The company should continue to expand in various business sectors in order to increase company’s assets and business development in the future